Computational analysis of copper@paraffin composite in a cylindrical cavity for enhanced thermal energy storage system. (2021) - Paneliya, Sagar; Khanna, Sakshum; Prajapati, Parth; Borad, Arpitkumar
Abstract: The present study shows a comparative behavior and thermal performance of the paraffin and copper-doped paraffin composite in a cylindrical cavity system with a heat source. The primary objective is to improve the heat storage capacity using metal (copper) particles due to their high thermal conductivity. A computational fluid dynamic model with physical enthalpy formulation has been used to predict paraffin-copper composite behavior as phase change material to absorb and store heat energy at given operating conditions. The progression of temperature and liquid liquefaction fraction for the cylindrical cavity filled with different PCM's at an applied temperature (Th  = 350 K) has been carried out during the study. Temperature and liquid fraction measurement were studied, and it was observed that configuration with copper-doped paraffin composite showed enhanced heat transfer as compared to pure paraffin and reduced its liquefaction time from 5000 s to 2400 s. Reduction in liquefaction time signifies improved heat transfer between the base fluid and PCM and may serve as next generation PCM for energy storage.